Fighting the War Within: A Look at Ontario Metis Life and the Creation of a New Standard Post-Powley - Lauzer, Shawn (Université d'Ottawa / University of Ottawa, 2012)
In Canada today there exists a new form of segregation towards the Métis people, called the Powley points. Because of it, Métis are being forced to become a different version of themselves, counter to their own personal identity, thereby creating a new standard of identity for Métis, one that not all Métis are able to meet because of historical factors. What the research shows is an over representation of Western Métis politics regarding Métis identity and the formation of it. I therefore, propose a change to the current status quo regarding how Métis are defined and how they are expected to define themselves within this system. For this thesis I rely primarily on archival research and textual analysis, such as journal articles, census data, and published material from the Métis organizations, to establish the current situation in Métis politics as well as my position regarding these issues.